Cambio, adaptación y resiliencia en el yacimiento arqueológico de El Laderón (Doña Mencía, Córdoba, España). Estudio de la terra sigillata procedente del Sector 4 del oppidum íbero-romano - Moreno Alcaide, Manuel; Ruiz Montes, Pablo; Serrano Arnáez, Begoña; Fernández-García, M.ª Isabel (Rei Cretariae Romanae Fautorum Acta, 2022)
This paper aims to study the commercial dynamics and globalization processes through the preliminary study of terra sigillata of Platform 1 of Sector 4 of the El Laderón archaeological site (Doña Mencía, Córdoba), belonging to the excavation campaign of the year 2017. Ceramics from Italic and Gallic workshops have been identified, as well as the Tritium pottery complex, which determines a long distance trade. On the other hand, the most significant number of materials is associated with the officinae of Isturgi (Los Villares de Andújar, Jaén) determining a medium and short distance trade.